Manipulation of safety training practices on organizational safety performance: anevidence in Malaysia's automotive industry - Abdul Wahab, Shah Rollah (2014)
This paper aims to investigate the role of safety training practices to safety performance in Malaysia’s automotive industry. This study adopts a non-experimental type research which employs questionnaire as the method of collecting data. The measurement tool undertaken in the data collection is Safety Performance Scale that developed by Wu et al. (2007). A total of 696 employees from Malaysia automotive manufacturing and assembly plants are selected as the respondents of this study. The selection of respondents is made using systematic sampling design. Data of the study are then analyzed using canonical correlation analysis. The finding of the study highlights that safety training practices plays a significant influence to an organization’s safety performance (r 2 = 0.631, p <0.001).